2012
DOI: 10.1093/jxb/err421
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive quantification of cereal roots in soil using high-resolution X-ray tomography

Abstract: One key constraint to further understanding plant root development is the inability to observe root growth in situ due to the opaque nature of soil. Of the present non-destructive techniques, computed tomography (CT) is best able to capture the complexities of the edaphic environment. This study compared the accuracy and impact of X-ray CT measurement of in situ root systems with standard technology (soil core washing and WinRhizo analysis) in the context of treatments that differed in the vertical placement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 29 publications
3
109
0
Order By: Relevance
“…1B). As MRI, root analysis with x-ray CT also acquires, with current root segmentation procedures, similar fractions of roots compared to WinRHIZO (Flavel et al, 2012;Metzner et al, 2015). Koebernick et al (2014) reported a detection of near 100% for roots of Vicia faba regarding only roots .500 mm.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1B). As MRI, root analysis with x-ray CT also acquires, with current root segmentation procedures, similar fractions of roots compared to WinRHIZO (Flavel et al, 2012;Metzner et al, 2015). Koebernick et al (2014) reported a detection of near 100% for roots of Vicia faba regarding only roots .500 mm.…”
Section: Discussionmentioning
confidence: 97%
“…Computed tomography (CT; both x-ray and neutron) has been proposed to overcome the mentioned difficulties with studying roots in natural soil. CT has been successfully used to obtain high-resolution images of roots (Moradi et al, 2009;Flavel et al, 2012;Mooney et al, 2012). High resolution is necessary for segmenting roots due to a poor contrast between roots and soil (Jassogne et al, 2009;Mairhofer et al, 2012;Mairhofer et al, 2013).…”
mentioning
confidence: 99%
“…Techniques to facilitate screening of roots across genotypes have been developed utilising both destructive and non-destructive methods (Flavel et al 2012), with the common objective of improving the adaptation of crops to both the biotic (Watt et al 2003;Sprague et al 2007) and abiotic soil factors (Rahnama et al 2011) which induce stress. These techniques need to be applied in the development of perennial forages to strengthen root systems and thereby enhance plant persistence, although so far few of the more advanced phenomic techniques have been applied with these species (Walter et al 2012).…”
Section: Dehydration Avoidance/delay and Rooting System Improvementmentioning
confidence: 99%
“…Increasingly, the imaging of plants at multiple time intervals is being incorporated into μCT studies, allowing longitudinal quantification of root trait development in relation to key soil parameters . Of particular relevance to this study is the application of such a time-resolved (or '4D') μCT approach to the investigation of elevated rooting density within soil areas of elevated P concentration (Flavel et al 2012). Previous research has noted that root proliferation can be locally up-regulated in the presence of P and N rich patches (Drew 1975;Hodge 2004), with μCT imaging now offering a promising means by which to assess the behaviour of plant roots to different types of P resource in soil.…”
Section: Introductionmentioning
confidence: 99%